STAM-AMSH interaction facilitates the deubiquitination activity in the C-terminal AMSH - Kim, Man Su; Kim, Jeom-A; Song, Hyun Kyu; Jeon, Hyesung (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2006)
Signal transducing adaptor molecule (STAM) complexed with hepatocyte growth factor regulated tyrosine kinase substrate (Hrs) works on sorting of cargo proteins in multivesicular body (MVB) pathway. Associated molecule with SH3 domain of STAM (AMSH), a zinc-containing ubiquitin isopeptidase, is thought to play a role in regulation of ubiquitin-mediated degradation by binding to STAM. We have found that AMSH requires the conformation of Px(V/I)(D/N)RxxKP sequence to bind SH3 domain of STAM with similar to 7 mu M affinity, and that the isolated C-terminal domain of AMSH contains the isopeptidase activity. Deubiquitination by AMSH was assisted when ubiquitins were bound to STAM which can bind to AMSH simultaneously. With the specificity toward K63-linked ubiquitins. this facilitated ubiquitin processing activity of AMSH may imply a distinct regulatory mechanism for sorting and degradation through STAM binding. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: RECEPTOR DOWN-REGULATION; SRC HOMOLOGY-3 DOMAIN; UBIQUITIN ISOPEPTIDASE; SH3 DOMAINS; MEMBRANE-PROTEINS; ENDOCYTIC PATHWAY; HRS; ENDOSOME; BINDING; TRANSPORT